Tribological Analysis and Optimization of Ring-Cylinder Couple Coated with Different Materials - Cesur, Idris; Akgündüz, Mehmet; Çelik, Hasan Ali; Çay, Yusuf; Ergen, Gökhan (Arabian journal for science and engineering (2011), 2024)
The performance and efficiency of internal combustion engines heavily rely on the tribological characteristics of the piston ring-cylinder couple. Various coating materials have been introduced to the piston ring and cylinder liner surfaces to enhance durability and reduce frictional losses. This study investigated the tribological properties of the piston ring coated with different materials between the cylinder-ring pair. The piston rings were coated with palladium (Pd) and manganese phosphate (Mg) materials using an electrochemical method. As a result of the experimental study, it has been determined that cylinder liner and ring specimens exposed to friction at low speeds are subject to more wear than at higher speeds. When comparing coated piston rings, it was found that the Pd-coated piston ring exhibited a lower coefficient of friction and wear rate compared to the Mg-coated piston ring. When the wear rates are examined at 30 °C and under 80 N load, an average of 27% reduction was observed for the Pd-coated ring compared to the Mg-coated ring and an average of 33% at 80 °C. According to the Chi-square test, the best results in ring wear rate were obtained with 40N load, 150 rpm, 80 °C temperature, and Pd-coated ring.